Cognitive Disputation Through Sholawat Burdah To Overcome Stress of a Santri In Pesantren - Ach. Andrian Maulana R; Mohamad Thohir (Interdisciplinary Journal of Social Sciences, 2024)
This article is based on an assessment conducted on a counselee who is currently a student at the Wustha level in Pesantren As-Salafi Al-Fithrah, Surabaya, experiencing difficulties in communication and adaptation due to the lack of support from their surroundings. This article aims to understand the implementation process and the outcomes of cognitive disputation using Sholawat Burdah to alleviate stress in a student at Pesantren As-Salafi Al-Fithrah, Surabaya. The research method used in this study is qualitative with a descriptive comparative research type. This study compares the counselee's behavior before and after receiving counseling services. The results of cognitive disputation using Sholawat Burdah to alleviate a student's stress can be seen from the changes in the counselee's behavior before and after the counseling sessions. Before counseling, the counselee experienced stress-related problems that affected concentration, caused restlessness, and made adaptation difficult. After the counseling process, behavioral changes were observed, such as the counselee being able to overcome feelings of inferiority with more self-confidence in social interactions, being calmer in dealing with situations, and being more courageous in interacting with others, especially new people in their lives. From this explanation, it can be concluded that cognitive disputation using Sholawat Burdah is effective in alleviating a student's stress.